Molten salt electrolysis method for preparing iron-encapsulated carbon nanotubes by using blast furnace dust and application of molten salt electrolysis method
By using molten salt electrolysis method prepared by blast furnace dust under simulated blast furnace flue atmosphere, the problem of uneven coating of magnetic metal element in traditional methods was solved, and carbon nanometers with uniform pipe diameter, long radial length and uniform iron element were prepared. The tube significantly improves microwave absorption performance.
Patent Information
- Application Number
- CN202411479760.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-07
AI Technical Summary
The traditional chemical vapor deposition method of preparing magnetized carbon nanotubes has the problem of uneven coating of magnetic metals, which affects the absorption performance of the material.
Using blast furnace dust as iron source, carbon nanotubes with encapsulated iron are prepared by molten salt electrolysis in simulated blast furnace flue atmosphere to ensure uniform pipe diameter, long radial length, uniform iron elemental quality, high graphitization degree, and improve microwave absorption performance .
Carbon nanotubes with uniform pipe diameter, long radial length, uniform iron elemental quality, high degree of graphitization and superior microwave absorption performance have been achieved. The problem of uneven coating in traditional methods has been overcome and the absorption of materials has been improved. performance.
Smart Images

Figure CN119265576A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon nano material preparation, and in particular to a molten salt electrolysis method for preparing iron-encapsulated carbon nanotubes using blast furnace dust and its application. Background Art
[0002] With the development of science and technology and the improvement of people's living standards, electronic equipment, military equipment, etc. play a vital role in both civil and military applications. The resulting electromagnetic pollution will affect people's health and the detection of military signals. In response to this phenomenon, people have effectively solved the problems of electromagnetic wave interference and harm to human health through in-depth research and development of materials that absorb electromagnetic waves. Absorbing materials refer to a type of material that can absorb electromagnetic wave energy projected onto its surface and convert electromagnetic energy into heat energy through the loss of the material. From the perspective of loss mechanism, absorbing materials can be divided into two categories: dielectric loss and magnetic loss. Carbon materials are a type of material that loses electromagnetic waves through the dielectric loss mechanism. Among them, carbon nanotubes (CNTs) have always been favored by researchers due to their light weight, high strength, and adjustable dielectric properties.
[0003] Although carbon nanotubes have a high dielectric constant and can be adjusted by some means, their low magnetic permeability often leads to impedance mismatch due to the large difference with the dielectric constant, which limits the microwave absorption capacity and makes it impossible to achieve effective absorption in a wider microwave frequency range. Ideal microwave absorption materials should have a wider absorption bandwidth, lower matching thickness, stronger absorption and lighter weight. Therefore, researchers have turned their attention to composite materials, combining carbon materials with traditional magnetic materials, and comprehensively utilizing the advantages of carbon materials such as light weight, high conductive loss and impedance matching of magnetic materials and good magnetic loss. Studies have shown that composite materials can have excellent microwave absorption performance under the synergistic effect and complementary effect between carbon materials and magnetic materials. Therefore, many studies have focused on the preparation of new composite materials using carbon nanotubes, among which the research on "magnetized carbon nanotubes" has attracted much attention. The so-called magnetized carbon nanotubes refer to carbon nanotubes filled or modified with magnetic particles. Such composite materials can rely on the synergistic effect of magnetic-dielectric loss to improve the impedance matching ability of the material and increase the loss capacity of microwaves. However, the traditional chemical vapor deposition method for preparing magnetized carbon nanotubes is limited by the high cost of carbon sources and metal catalysts.
[0004] In order to overcome these problems, there are some methods, such as CN110359068A, which uses molten salt electrolyte to electrolyze magnetic metal oxides and successfully prepares carbon nanotube-coated magnetic metal materials. However, the material prepared by this method has the problem of uneven coating of magnetic metal elements, which will have an adverse effect on the material's wave absorption performance. It is necessary to make corresponding improvements to the molten salt electrolysis method to prepare carbon nanotubes encapsulating magnetic metal elements with good coating effect and strong wave absorption performance. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention comprehensively utilizes blast furnace flue gas, adds the collected iron source into a molten salt system, and electrolyzes it under CO2 to simulate the blast furnace flue gas atmosphere, and prepares iron-encapsulated carbon nanotubes with uniform tube diameter, long radial length, uniform iron element, high degree of graphitization, and excellent microwave absorption performance through molten salt electrolysis.
[0006] In order to achieve the above object, the present invention provides a molten salt electrolysis method for preparing carbon nanotubes encapsulating iron using blast furnace dust, comprising: adding an iron source into the molten salt and melting the iron source; After the iron source is completely melted, electrolysis is continued under the condition of introducing CO2 to simulate the blast furnace flue gas atmosphere. After the electrolysis is completed, the carbon nanotubes encapsulating the iron are collected; Wherein, the iron source is obtained by collecting and processing blast furnace dust.
[0007] Preferably, the molten salt is obtained by melting the corresponding salt under an inert gas atmosphere at elevated temperature.
[0008] Specifically, after the electrolysis is completed, the deposited products on the cathode electrode are collected and then impurities are removed to obtain carbon nanotubes encapsulating iron. The impurity removal includes pickling. The acid solution used for the pickling does not need to be strictly limited, and is illustratively selected from a mixed aqueous solution of at least one of hydrochloric acid, sulfuric acid, and acetic acid. At the same time, the concentration of the acid solution does not need to be strictly limited, and it can be prepared according to the needs.
[0009] Blast furnace dust is powder and particulate matter produced by blast furnace gas dust removal in the iron-making industry. The elemental composition of blast furnace dust is closely related to the chemical composition of pig iron ore, the fuel charged into the blast furnace and the process conditions. But in general, iron and carbon are the main elements in blast furnace dust. Among them, iron mainly exists in the form of iron oxide, such as FeO, Fe2O3 and Fe3O4; it may also include a small amount of FeS, FeS2, Fe2S3. Specifically, FeO, Fe2O3, Fe3O4, FeS, FeS2, Fe2S3 can be obtained by separating and purifying blast furnace dust, and at least one of these substances can be used as an iron source. That is, the iron source of the present invention includes at least one of FeO, Fe2O3, Fe3O4, FeS, FeS2, and Fe2S3.
[0010] The design concept of the present invention is that CO2 can be converted into O in molten salt at high temperature. 2- Rapid ion capture to generate CO3 2- ions, coupled with the low melting point, wide liquid range, and wide electrochemical window of molten salt, CO3 2- The iron source can easily overcome the energy barrier under the high temperature of the applied overpotential and be reduced to carbon and iron elements at the cathode. While reducing carbon emissions, it can achieve co-electrolysis of CO2 and metal oxides, realize iron encapsulation, and obtain iron-encapsulated carbon nanotubes.
[0011] Furthermore, the iron source accounts for 0.2%-2% of the mass of the molten salt.
[0012] Furthermore, the molten salt includes at least one of molten salts of alkali metal chlorides, alkaline earth metal chlorides, alkali metal carbonates, and alkaline earth metal carbonates.
[0013] In order to avoid the generation of toxic chlorine gas during high potential electrolysis of alkali metal chloride salts and alkaline earth metal chloride salts.
[0014] Furthermore, the molten salt is carbonate of alkali metal and carbonate of alkaline earth metal, wherein the carbonate of alkaline earth metal accounts for 5%-10% of the mass of all carbonates.
[0015] Preferably, the carbonate of alkali metal is selected from Na2CO3 and K2CO3, and the molar ratio of Na2CO3 to K2CO3 is 0.5-2:1; the carbonate of alkaline earth metal is at least one of CaCO3, MgCO3, SrCO3, and BaCO3.
[0016] Furthermore, the CO2 inlet flow rate is 50-300 mL / min.
[0017] Furthermore, the electrolysis is continued for 0.5-6h at a voltage of 2.0-3.0V and a temperature of 700-950°C.
[0018] In the present invention, the anode used in electrolysis is made of an inert anode material that can be stable in carbonates, can convert absorbed carbon dioxide into oxygen, and precipitate oxygen at the anode. For example, the material used in the anode can be Ni10Cu11Fe alloy, SnO2, and graphite, amorphous carbon, carbon obtained by pyrolysis of biomass, carbon nanotubes, graphene, graphite oxide or reduced oxidized graphene. The material of the cathode used in electrolysis is at least one of stainless steel, Ni, Mo, W, Fe, Cu, and carbon paper.
[0019] The method further includes pre-electrolyzing the molten salt before adding the iron source into the molten salt; The pre-electrolysis lasts for 1-3 hours at 2.0-3.0 V. The electrode materials used in the pre-electrolysis and the electrolysis are the same or different. Preferably, after the pre-electrolysis is completed and the iron source is completely melted, the cathode electrode is also replaced. For example, a Ni sheet electrode is used in the pre-electrolysis, and a new Ni sheet electrode or a carbon paper electrode can be used in the electrolysis.
[0020] The present invention also provides an iron-encapsulated carbon nanotube, which is prepared by the molten salt electrolysis method for preparing the iron-encapsulated carbon nanotube using blast furnace dust.
[0021] The present invention also provides the use of the above-mentioned iron-encapsulated carbon nanotubes as microwave absorbing materials.
[0022] Compared with the prior art, the present invention has the following beneficial effects: The present invention makes comprehensive use of blast furnace flue gas, adds the collected iron source into a molten salt system, and continuously electrolyzes the system while introducing CO2 to simulate the blast furnace flue gas atmosphere. After the electrolysis, carbon nanotubes encapsulating iron with uniform tube diameter, long radial length, uniform iron element, high degree of graphitization, and excellent microwave absorption performance are obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 shows the X-ray diffraction pattern of Fe@CNTs prepared in Example 1; Figure 2 shows a scanning electron microscope image of Fe@CNTs prepared in Example 1; Figure 3 shows a transmission electron microscopy image of Fe@CNTs prepared in Example 1; Figure 4 shows the scanning electron microscopy images of Fe@CNTs prepared in Examples 2-4; Figure 5 The scanning electron microscope image of Fe@CNTs prepared in Comparative Example 2 is shown; Figure 6 The electromagnetic wave reflection loss comparison graph of the materials prepared in Examples 1-4 is shown; Figure 7 A comparison graph of electromagnetic wave reflection losses of materials prepared in Example 1 and Comparative Examples 1 and 2 is shown. DETAILED DESCRIPTION
[0025] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0026] The following will be combined with the specific embodiments of the present invention and the drawings of the specification to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1 A molten salt electrolysis method for preparing iron-encapsulated carbon nanotubes using blast furnace dust, the steps are as follows: S1. Weigh 450g of NaCO3-K2CO3 mixed salt (wherein the molar ratio of NaCO3 and K2CO3 is 59:41) as electrolyte, heat the electrolyte to 750℃ in an argon atmosphere to melt, then add 5% CaCO3 by mass of the mixed salt to mix well to obtain molten salt, use a Ni sheet with a length of 20mm, a width of 10mm and a thickness of 1mm as the cathode electrode, and a columnar Ni10Cu11Fe with a length of 20mm and a diameter of 10mm as the anode electrode, and pre-electrolyze the molten salt at a voltage of 1.8V for 2h; S2. After the pre-electrolysis, the molten salt temperature was maintained at 750°C, and 3g of Fe3O4 was added to the molten salt. Fe3O4 was collected and processed from blast furnace dust. After the Fe3O4 was completely melted, the cathode electrode was replaced with a new Ni sheet with a length of 20mm, a width of 10mm and a thickness of 1mm. The anode electrode remained unchanged, and CO2 was introduced at a flow rate of 100mL / min to simulate the blast furnace flue gas atmosphere. Electrolysis was carried out at a molten salt temperature of 700°C and a voltage of 2.4V for 2h. After the electrolysis was completed, the deposited product on the cathode electrode was collected and washed with a 1mol / L acetic acid aqueous solution. The insoluble matter was collected by centrifugation and dried at 120°C to obtain iron-encapsulated carbon nanotubes (Fe@CNTs).
[0028] Example 2-Example 4 It is basically the same as Example 1, except that the voltages during electrolysis in step S2 are 2.0V, 2.2V, and 2.6V respectively.
[0029] Example 5-Example 7 It is basically the same as Example 1, except that the time for electrolysis in step S2 is 0.5h, 2h, and 3h respectively.
[0030] Example 8 A molten salt electrolysis method for preparing iron-encapsulated carbon nanotubes using blast furnace dust, the steps are as follows: S1. Weigh 450g of NaCO3-K2CO3 mixed salt (wherein the molar ratio of NaCO3 and K2CO3 is 59:41) as electrolyte, heat the electrolyte to 800℃ in an argon atmosphere to melt, then add CaCO3 and mix to obtain molten salt, the amount of CaCO3 added is 10% of the total mass of the molten salt, use a Ni sheet with a length of 20mm, a width of 10mm, and a thickness of 1mm as the cathode electrode, and a columnar SnO2 with a length of 20mm and a diameter of 10mm as the anode electrode, and pre-electrolyze the molten salt at a voltage of 1.8V for 2h; S2. After the pre-electrolysis, the molten salt temperature was maintained at 750°C, and 2g of FeO and 1g of FeS were added to the molten salt. FeO and FeS were collected and processed from blast furnace dust. After FeO and FeS were completely melted, the cathode electrode was replaced with a new Ni sheet with a length of 20mm, a width of 10mm, and a thickness of 1mm. The anode electrode remained unchanged, and CO2 was introduced at a flow rate of 100mL / min to simulate the blast furnace flue gas atmosphere. Electrolysis was carried out at a molten salt temperature of 800°C and a voltage of 2.4V for 2h. After the electrolysis was completed, the deposited products on the cathode electrode were collected and washed with a 1mol / L acetic acid aqueous solution. The insoluble matter was collected by centrifugation and dried at 120°C to obtain Fe@CNTs.
[0031] Example 9 A molten salt electrolysis method for preparing iron-encapsulated carbon nanotubes using blast furnace dust, the steps are as follows: S1. Weigh 450g of NaCO3-K2CO3 mixed salt (wherein the molar ratio of NaCO3 and K2CO3 is 59:41) as electrolyte, heat the electrolyte to 850℃ in an argon atmosphere, then add BaCO3 and mix to obtain molten salt, the amount of BaCO3 added is 10% of the total mass of the molten salt, use a Ni sheet with a length of 20mm, a width of 10mm and a thickness of 1mm as the cathode electrode, and a columnar Ni10Cu11Fe with a length of 20mm and a diameter of 10mm as the anode electrode, and pre-electrolyze the molten salt at a voltage of 1.8V for 2h; S2. After the pre-electrolysis, the molten salt temperature was maintained at 850°C, and 2g of Fe3O4 and 1g of FeS were added to the molten salt. Fe3O4 and FeS were collected and processed from blast furnace dust. After Fe3O4 and FeS were completely melted, the cathode electrode was replaced with a new Ni sheet with a length of 20mm, a width of 10mm and a thickness of 1mm. The anode electrode remained unchanged, and CO2 was introduced at a flow rate of 100mL / min to simulate the blast furnace flue gas atmosphere. Electrolysis was performed at a molten salt temperature of 850°C and a voltage of 2.4V for 2h. After the electrolysis was completed, the deposited product on the cathode electrode was collected and washed with a 2mol / L acetic acid aqueous solution. The insoluble matter was collected by centrifugation and dried at 120°C to obtain Fe@CNTs.
[0032] Example 10 A molten salt electrolysis method for preparing iron-encapsulated carbon nanotubes using blast furnace dust, the steps are as follows: S1. Weigh 450 g of NaCO3-K2CO3 mixed salt (wherein the molar ratio of NaCO3 and K2CO3 is 59:41) as electrolyte. In an argon atmosphere, heat the electrolyte to 750°C to melt, then add SrCO3 and mix to obtain molten salt. The amount of SrCO3 added is 10% of the total mass of the molten salt. Use a Mo sheet with a length of 20 mm, a width of 10 mm, and a thickness of 1 mm as the cathode electrode, and a columnar SnO2 with a length of 20 mm and a diameter of 10 mm as the anode electrode. Pre-electrolyze the molten salt at a voltage of 1.8 V for 2 hours; S2. After the pre-electrolysis, the molten salt temperature was maintained at 750°C, and 2g of Fe3O4 and 1g of FeS were added to the molten salt. Fe2O3 and FeS were collected and processed from blast furnace dust. After the Fe2O3 was completely melted, the cathode electrode was replaced with a new Mo sheet with a length of 20mm, a width of 10mm and a thickness of 1mm. The anode electrode remained unchanged, and CO2 was introduced at a flow rate of 100mL / min to simulate the blast furnace flue gas atmosphere. The electrolysis was carried out at a molten salt temperature of 750°C and a voltage of 2.6V for 2h. After the electrolysis was completed, the deposited products on the cathode electrode were collected and washed with a 2mol / L acetic acid aqueous solution. The insoluble matter was collected by centrifugation and dried at 120°C to obtain Fe@CNTs.
[0033] Embodiment 11 A molten salt electrolysis method for preparing iron-encapsulated carbon nanotubes using blast furnace dust, the steps are as follows: S1. Weigh 450 g of NaCO3-K2CO3 mixed salt (wherein the molar ratio of NaCO3 and K2CO3 is 59:41) as electrolyte, heat the electrolyte to 780°C in an argon atmosphere to melt, then mix MgCO3 to obtain molten salt, the amount of MgCO3 added is 5% of the total mass of the molten salt, use a Mo sheet with a length of 20 mm, a width of 10 mm, and a thickness of 1 mm as the cathode electrode, and a columnar SnO2 with a length of 20 mm and a diameter of 10 mm as the anode electrode, and pre-electrolyze the molten salt at a voltage of 1.8 V for 2 hours; S2. After the pre-electrolysis, the molten salt temperature was maintained at 780°C, and 3g of Fe2O3 was added to the molten salt. The Fe2O3 was collected and processed from blast furnace dust. After the Fe2O3 was completely melted, the cathode electrode was replaced with a new Mo sheet with a length of 20mm, a width of 10mm and a thickness of 1mm. The anode electrode remained unchanged, and CO2 was introduced at a flow rate of 100mL / min to simulate the blast furnace flue gas atmosphere. The electrolysis was carried out at a molten salt temperature of 780°C and a voltage of 2.6V for 2h. After the electrolysis was completed, the deposited product on the cathode electrode was collected and washed with a 1mol / L acetic acid aqueous solution. The insoluble matter was collected by centrifugation and dried at 120°C to obtain Fe@CNTs.
[0034] Comparative Example 1 A molten salt electrolysis method for preparing carbon nanotubes, the steps are as follows: T1. Weigh 450 g of NaCO3-K2CO3 mixed salt (wherein the molar ratio of NaCO3 and K2CO3 is 59:41) as electrolyte. In an argon atmosphere, heat the electrolyte to 700°C to melt, then add CaCO3 and mix to obtain molten salt. The amount of CaCO3 added is 5% of the total mass of the molten salt. Use a Ni sheet with a length of 20 mm, a width of 10 mm, and a thickness of 1 mm as the cathode electrode, and a columnar Ni10Cu11Fe with a length of 20 mm and a diameter of 10 mm as the anode electrode. Pre-electrolyze the molten salt at a voltage of 1.8 V for 2 h. T2. After the pre-electrolysis, the molten salt temperature was maintained at 700°C, the cathode electrode was replaced with a new Ni sheet with a length of 20 mm, a width of 10 mm and a thickness of 1 mm, the anode electrode remained unchanged, CO2 was introduced at a flow rate of 100 mL / min, and electrolysis was carried out for 2 hours at a molten salt temperature of 700°C and a voltage of 2.4 V; after the electrolysis was completed, the deposited product on the cathode electrode was collected and washed with a 1 mol / L acetic acid aqueous solution, the insoluble matter was collected by centrifugation and dried at 120°C to obtain carbon nanotubes.
[0035] Comparative Example 2 A molten salt electrolysis method for preparing iron-encapsulated carbon nanotubes using blast furnace dust, the steps are as follows: T1. Weigh 450 g of NaCO3-K2CO3 mixed salt (wherein the molar ratio of NaCO3 and K2CO3 is 59:41) as electrolyte. In an argon atmosphere, heat the electrolyte to 750°C to melt, then add CaCO3 and mix to obtain molten salt. The amount of CaCO3 added is 5% of the total mass of the molten salt. Use a Ni sheet with a length of 20 mm, a width of 10 mm, and a thickness of 1 mm as the cathode electrode, and a columnar graphite oxide rod with a length of 20 mm and a diameter of 15 mm as the anode electrode. Pre-electrolyze the molten salt at a voltage of 12.0 V for 2 h. T2. After the pre-electrolysis, the molten salt temperature is maintained at 750°C, and 3g of Fe3O4 is added to the molten salt. Fe3O4 is collected and processed from blast furnace dust. After the Fe3O4 is completely melted, the cathode electrode is replaced with a new graphite sheet with a length of 20mm, a width of 10mm and a thickness of 1mm. The anode electrode remains unchanged. Electrolysis is carried out at a molten salt temperature of 750°C and a voltage of 2.4V for 2h. After the electrolysis is completed, the deposited product on the cathode electrode is collected and washed with a 1mol / L acetic acid aqueous solution. The insoluble matter is collected by centrifugation and dried at 120°C to obtain Fe@CNTs.
[0036] Test Case The crystal structure of Fe@CNTs prepared in Example 1 was observed by X-ray diffractometer. Figure 1 As shown, it can be seen that the diffraction peaks of graphite phase carbon and iron with higher diffraction intensity appear. This result at least indicates the successful preparation of carbon materials with high degree of graphitization and containing iron element.
[0037] The microstructure of Fe@CNTs prepared in Example 1 was observed by scanning electron microscopy. Figure 2 As shown, Figure 2 (a) and (2)b have different scales. Figure 2 (a) and Figure 2 (b) and combination Figure 1 , illustrating the preparation of iron-coated carbon nanotube materials with a morphology of small tube diameter and long radial length.
[0038] The microstructure of Fe@CNTs prepared in Example 1 was further observed using a transmission microscope. Figure 3 As shown, it can be seen that elemental iron is uniformly filled in the carbon nanotube structure.
[0039] The microstructures of Fe@CNTs prepared in Examples 2-4 at different electrolysis voltages were further observed using a scanning electron microscope. Figure 4 As shown, Figure 4 (a) indicates that the samples prepared by electrolysis at 2.0 V are mainly nanoparticles, and Figure 4(b) The sample prepared by electrolysis at 2.2 V has a preliminary tubular morphology, but the low voltage is still not enough to guide the complete formation of carbon nanotubes. Figure 4 (c) shows that the sample prepared by electrolysis at a high voltage of 2.6 V has a thicker tube diameter and a shorter tube diameter. This may be due to the excessive generation of CaC2 by CaCO3 electrolysis under high voltage electrolysis conditions. CaC2 can serve as a nucleation site to guide the excessive growth of carbon nanotubes. Therefore, combined with Figure 2-4 , indicating that the material prepared in Example 1 has an excellent morphology with small tube diameter and long radial length.
[0040] The mechanism of growing carbon nanotubes of the present invention is as follows: in the system of carbonate (XCO3, X=at least one of Ca, Mg, Sr, Ba) and iron source under the condition of applied voltage, three reactions will occur at the cathode: (1) the iron source is converted into Fe; (2) XCO3 is converted into XO and C; (3) XCO3 is converted into XC2 and XO. According to thermodynamic results, the cathode generation reaction of XC2 occurs at a lower voltage than the deposition of X, indicating that XC2 is more conducive to guiding the nucleus of CNT generation. Therefore, under a suitable voltage, XCO3 is electrolyzed to generate XC2 and guide the subsequent electrolysis of XC2 to generate C in the form of a tube. It is worth mentioning that the XO generated by the electrolysis of XCO3 will capture the CO2 introduced externally and generate XCO3 again, which provides a continuous source of raw materials for the growth of carbon nanotubes. At the same time, the iron source and the XCO3 generated by CO2 will be co-reduced to encapsulate Fe in CNT through the nucleation process mediated by XC2, and Fe@CNT is successfully prepared.
[0041] The microstructure of Fe@CNTs prepared in Comparative Example 2 was observed using a scanning electron microscope. Figure 5 As shown, it can be seen that the metal is filled into the coating structure of the carbon nanotube, but there is a phenomenon of some nanoparticles attached near the tube. Figure 2 and Figure 5 , further illustrating that the material prepared in Example 1 has smooth tube walls, uniform tube diameters and high surface density. Figure 2-Figure 5 This indicates that the electrolysis voltage and the introduction of exogenous CO2 have significant effects on the aspect ratio of Fe@CNTs and the inhibition of the adhesion of iron nanoparticles. Only under the conditions of appropriate voltage and CO2 introduction can Fe@CNTs with uniform coating and high aspect ratio be prepared.
[0042] Reflection loss is an important indicator for evaluating the reflection performance of microwave absorbing materials. It is generally used to describe the reflection of incident waves by the material. The reflection loss of the materials prepared in Examples 1-4 was tested. The thickness of the coating on the tested samples was 2.2 mm. The results are as follows: Figure 6As shown, it can be seen that the Fe@CNTs prepared in Example 1 has stronger microwave absorption and wider absorption bandwidth than the samples prepared in Examples 2-4, with the best microwave reflection loss of -44.7dB and the frequency bandwidth with reflection loss lower than -10dB (electromagnetic wave absorption of more than 90%) being 4.7GHz. Therefore, combined with the above characterization, it can be seen that the uniformity of the morphology of the iron-coated carbon nanotubes is one of the important factors that determine the quality of its microwave absorption performance.
[0043] The reflection loss of the materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 was also tested. The thickness of the coating on the tested samples was 2 mm. The results are as follows: Figure 7 As shown, it can be seen that the Fe@CNTs prepared in Example 1 have stronger microwave absorption and wider absorption bandwidth than the carbon nanotubes prepared in the comparative example.
[0044] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A molten salt electrolysis method for preparing iron-encapsulated carbon nanotubes using blast furnace dust, characterized in that: include, adding an iron source to the molten salt; After the iron source is completely melted, electrolysis is continued under the condition of introducing CO2 to simulate the blast furnace flue gas atmosphere. After the electrolysis is completed, the carbon nanotubes encapsulating the iron are collected; Wherein, the iron source is obtained by collecting and processing blast furnace dust.
2. The molten salt electrolysis method for preparing iron-encapsulated carbon nanotubes using blast furnace dust according to claim 1, characterized in that: The iron source accounts for 0.2%-2% of the mass of the molten salt; The iron source includes at least one of FeO, Fe2O3, Fe3O4, FeS, FeS2, and Fe2S3.
3. The molten salt electrolysis method for preparing iron-encapsulated carbon nanotubes using blast furnace dust according to claim 1, characterized in that: The molten salt includes at least one of molten salts of alkali metal chloride, alkaline earth metal chloride, alkali metal carbonate, and alkaline earth metal carbonate.
4. The molten salt electrolysis method for preparing iron-encapsulated carbon nanotubes using blast furnace dust according to claim 3, characterized in that: The molten salt is carbonate of alkali metal and carbonate of alkaline earth metal, wherein the carbonate of alkaline earth metal accounts for 5%-10% of the mass of all carbonates.
5. The molten salt electrolysis method for preparing iron-encapsulated carbon nanotubes using blast furnace dust according to claim 1, characterized in that: The CO2 inlet flow rate is 50-300 mL / min.
6. The molten salt electrolysis method for preparing iron-encapsulated carbon nanotubes using blast furnace dust according to claim 1, characterized in that: The electrolysis is continued for 0.5-6 hours at a voltage of 2.0-3.0 V and a temperature of 700-950° C.
7. The molten salt electrolysis method for preparing iron-encapsulated carbon nanotubes using blast furnace dust according to claims 1-6, characterized in that: The method further includes pre-electrolyzing the molten salt before adding the iron source into the molten salt; The pre-electrolysis lasts for 0.5-3 h at 2.0-3.0 V.
8. An iron-encapsulated carbon nanotube, characterized in that: The carbon nanotubes encapsulating iron are prepared by the molten salt electrolysis method for preparing carbon nanotubes encapsulating iron using blast furnace dust as described in any one of claims 1 to 7.
9. Use of the iron-encapsulated carbon nanotubes according to claim 8 as microwave absorbing materials.
Citation Information
Patent Citations
Method for preparing carbon nano tube coated metal material based on molten salt electrochemical method
CN110359068A